Metode Loop-Mediated Isothermal Amplification (LAMP) dan Aplikasinya untuk Deteksi Penyakit Ikan - Murwantoko Murwantoko (Universitas Gadjah Mada, 2006)
Polymerase chain reaction (PCR) is a method that amplifies DNA which have been widely used in molecular biology technique. Based on the PCR, many methods have been developed on isothermal condition and the useful one is loop-mediated isothermal amplification of DNA (LAMP). LAMP reaction employs a Bst DNA polymerase and a set of four specific primers that recognizes a total of six distinct sequences of the target DNA and produces amount of different size of DNA. Many advantages have been achieved in LAMP such as the simple equipment for reaction and observation, short time, highly specific and sensitive procedure. LAMP has been used as a tools for detection many pathogens for human, animals and plants. Some fish pathogens as parasites, bacteria and viruses have been detected by LAMP. The principles and application of LAMP method are discussed in this paper.